Les usagers d’une plage péri-urbaine face à la contamination microbiologique des eaux de baignade - Maëlig Le Béguec; Emmanuelle Petit; Luc Vacher; Hélène Agogué; Mery Ndione (VertigO)
This paper deals with the case of a long-term swimming ban on a beach in the urban area of La Rochelle on the French Atlantic coast due to recurring exceedances of sanitary standards regarding water quality. It questions the confrontation of a coastal urban population with an environmental contamination issue in a space usually practiced for leisure activities. This analysis is presented through an environmental geography approach considering nature-society interactions and focusing on the perception of environmental quality in the attractiveness of coastal areas. Through the presentation of a survey’s results conducted among the local population, the aim is to analyze the way in which the user population perceives the alteration of the environmental quality of the beach and the bathing water and whether their understanding is homogeneous. The ways in which the origin of the contamination and the prevention dimension of the prohibition measures affect the population's understanding are presented. The changes in the practice of the beach and in the perception of this leisure space are related to the mode of information reception on the environment’s contamination. The roles of memory effect and place attachment that lead to the maintenance of certain practices will also be presented.